The Role of ERP Capabilities in Achieving Competitive Advantage: An Empirical Study on Dakahlia Governorate Companies, Egypt. Issue 4 (17th February 2019) - Elgohary, Esam
Abstract: Nowadays enterprise resource planning (ERP) systems are crucial for each company to automate and manage its business seamlessly and possess a competitive advantage. This paper was conducted with the purpose of determining which ERP capabilities categorized in IT capabilities, including integration, information access, IT skills and agility, and organizational capabilities including qualified human resources, top management support can affect decision‐making efficiency and competitive advantage types (low cost advantage and/or differentiation advantage), it also examines the impact of decision‐making efficiency on competitive advantage types. The problem of this paper is summarized in the uncertainty of the relationship between ERP capabilities and competitive advantage, as well as the absence of studies in this field. So, a survey was applied on 162 companies in Dakahlia Governorate, Egypt in order to investigates the impact of ERP capabilities on low‐cost advantage, differentiation advantage, and decision making efficiency, in order to determine whether each category of ERP capabilities can affect any competitive advantage type and decision‐making efficiency in itself or they must be combined with each other to occur impact, and finally examine the decision making efficiency impact on competitive advantage types.